Antimony Nanopolyhedrons with Tunable Localized Surface Plasmon Resonances for Highly Effective Photoacoustic-Imaging-Guided Synergistic Photothermal/Immunotherapy - Chen, Yu (Advanced materials (Deerfield Beach, Fla.), 2021)
© 2021 Wiley-VCH GmbH.